Risk Oriented Design of Protective Highway Structures - Egidijus R. Vaidogas (The Baltic Journal of Road and Bridge Engineering, 2007)
The problem of risk-based design of protective highway structures is considered. It is stated that the accidents involving damage to components of road infrastructure are a natural subject of a quantitative risk analysis. The paper discusses how to apply a risk oriented approach to the design of protective components of road infrastructure. A simulation- based procedure developed for a design of a protective highway structure by means of a multi-attribute selection is suggested. Attention is focused on uncertainties related to both accidental actions, which must be sustained by the protective structure, and behaviour of the structure under these actions. The proposed procedure serves for a comparison of alternative designs of the protective structure. The comparison takes into account epistemic uncertainties in failure-to-protect probabilities related to the alternative designs. It is shown that the multi-attribute selection can be carried out as a simulation- based propagation of the epistemic uncertainties. A loop of such simulation must involve deterministic algorithm of the multi-attribute selection. Repeating this loop a number of times yields relative frequencies of selecting individual alternative designs as the best ones. The optimal alternative design can be chosen as a design with the largest frequency of selection.